PROPOSE RELATIONSHIP MARKETING STRATEGY FOR BAYARIN.CO.ID COMPANY (The Indonesian Journal of Business Administration, 2019)
Indonesia PPOB market growing in good term make a new player in this industry increasing year by year to take market opportunity and the government policy which aim to make 75% of Indonesia adult people has banking service in 2019, this lead to make competition become tight for every player in PPOB industry. Instead of taking new customer the company need a strategy to maintain their customer to not move to competitor. relationship marketing (RM) strategy focus on how the company maintain their customer in such condition with fulfill the relationship marketing factor that is relational factor, competence factor and market offering factor. The research method is qualitative method to explore the company current condition of relationship marketing factor and literature review. The solution for this research will generate several alternative for each gap in the RM-factor and discussed with the kiosk and company to find the best solution for company which is improve the company marketing mix based on the discussion. The study shows how the three RM-factor related each other which is the company need to overcome each gap in every RM-factor to make strategy successful implemented in the company.Keywords:  Maintain kiosk, Marketing mix,PPOB industry, Relationship marketing, Marketing Strategy.